รำโจ๋ง ตำบลท่าโรง อำเภอวิเชียรบุรี จังหวัดเพชรบูรณ์ - นิศากานต์ ชอุ่ม (จุฬาลงกรณ์มหาวิทยาลัย, 2022)
The thesis on the topic of JONG DANCE: A CASE STUDY AT THARONG SUBDISTRICT, WICHIAN BURI DISTRICT, PHETCHABUN PROVINCE, aims to study the history of playing and dancing, as well as to analyze the components of the Jong dance play in Tharong Subdistrict, Wichian Buri District, Phetchabun Province The researcher utilized a research process involving the study of research documents, interviews, and field observations of the performances. The research findings revealed that Jong Dance evolved from Ram Thon, approximately after World War 2, by Mr. Thawat thupmongkhon, who showcased it in the village. Since then, it has gained popularity and has been performed during the Songkran festival around the year 2019. Khun Kanchana Thongma, the administrator of Kanchana Kindergarten School, has been instrumental in promoting this playful dance by introducing it as a training course for students. Starting from the year 2021 to the present, the Wichian Buri district culture has allocated a budget for the training program, focusing on dance performances for student representatives from Kindergarten to primary school levels in Tha Rong District, Wichian BuriDistrict, Phetchabun Province. These students learned and inherited the performance techniques from a dance expert to ensure its continuity. The dance features two groups of dancers. The male performers assume the role of cows and dance in the inner circle, while the female performers portray cow herders and dance in the outer circle. The dance is performed in a counter-clockwise direction and is accompanied by the rhythmic beat of the tone. The male dancers wear loincloths and girdles, while the female dancers wear long-sleeved shirts, breast cloths, and loincloths. Jong Dance is currently being broadcasted and the dance is being preserved as a part of the school curriculum to safeguard and pass down the local performance traditions in Tha Rong Subdistrict, Wichian Buri District, Phetchabun Province, thereby ensuring the continuity and preservation of this cultural heritage.